Aristotle on Sports and Competition: A Conversation with Today - Doukas, Panagiotis (Conatus - Journal of Philosophy, 2018)
In this paper I will present Aristotle’s views on sports. In particular, I will focus on why and how Aristotle rejects the one-dimensional physical exercise of athletes, advocating the ideal of "benevolence", that is, the necessity of harmonized mental and physical cultivation through gymnastics.